Pengaruh Model Pembelajaran Koperatif Tipe Make A Macth dengan Permainan Rangking One Physical Terhadap Motivasi dan Hasil Belajar Siswa - Sriwahyuningsih, Devi; Ahzan, Sukainil; Habiburrahman, Lalu (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2018)
[Title: The Effect of Cooperative Learning Model Type Make A Match with One Physical Ranking Game Toward Student Motivation and Learning Outcomes]. This study aims to determine the effect of cooperative learning model type make a macth with ranking one physical game on student motivation and learning outcomes. This research is quasi-experiment with pretest-posttest control group design. Population in this research is all students of class VII SMPN 2 Dompu which amounted to 124 people. Research sample consists of two classes that are class VII A which amounted to 30 people as control class and class VII B totalling 30 people as experimental class taken using random sampling technique. The results showed that homogeneity test and normality of learning motivation data and student learning outcomes were normally distributed and variance of both homogeneous data. This data is then analyzed using t-test, obtained tcount for learning motivation is 2,318 and ttable 2,002 or can be written mathematically is tcount> ttabel. While the learning results obtained tcount = 4.152 and ttabel = 2.002 or can be written mathematically is tcount> ttable at 5% significant level. The results of this study indicate that there is the influence of cooperative learning model type make a macth with ranking one physical game of student motivation and learning outcomes.